EKG Context Explorer: uma ferramenta gráfica para exploração baseada em contexto da Visão Semântica de um EKG - Freitas, José Renato da Silva (2024)
An Enterprise Knowledge Graph (EKG) serves as a robust foundation for knowledge management, data integration, and advanced analytics in organizations. This work focuses on the Semantic View of the Semantic Integration Layer of EKGs. The Semantic View is the result of the semantic integration of various data sources in the organization. The main contribution of this work is a framework for the construction and exploration of the Semantic View. The proposed framework provides a robust approach to effectively deal with most semantic data integration challenges. Firstly, an architecture to organize Semantic View data and metadata is proposed. Next, each level of the Semantic View architecture is detailed, presenting the definitions of its elements, where a real case study was used to demonstrate how the data graph is generated based on the Semantic View specification. The contribution of this framework is also the development of an interactive graphical interface, designed to explore the resources in the Semantic View in its different contexts. Another contribution of this work involves the construction of a dedicated vocabulary that describes the Semantic View metadata and how this vocabulary can help builders and consumers of EKGs.